Milestones over the development of SB3, a trastuzumab biosimilar. (21st June 2018) - Pivot, Xavier; Bondarenko, Igor; Petit, Thiery; Curtit, Elsa
The development of a biosimilar requires large extensive preclinical and clinical comparability exercises to demonstrate equivalence to the reference medical product. The holistic results from this large assessment should be taken into account to appreciate the validity of the development and the interpretations. SB3 is the first trastuzumab biosimilar approved for routine use in Europe. The present manuscript reviews the development and the results of SB3, including clinical assessment and the clinical Phase I, as well as the large randomized Phase III comparing efficacy between SB3 versus Herceptin ® containing regimen in neoadjuvant setting. Key points of the design and interpretations of the findings are extensively discussed in this review of SB3 development.